Physical Characteristic of Heat Resistant Chocolate Formulated with Konjac Glucomannan and Xanthan Gum-Based Hydrogel at Various Fat Content during Period of Crystal Growth (Maturation) - Arifin Dwi Saputro; Mira Aprilia Nur Fadilah; Samuel Keegen Bangun; Sri Rahayoe; Joko Nugroho Wahyu Karyadi; Arima Diah Setiowati (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2022)
Indirect addition of water into chocolate may form secondary sugar networks. This condition creates an increased melting temperature of chocolate. The purpose of this study was to increase the melting point of premium couverture chocolate without addition of fat/oil from other sources.  Chocolate was formulated with coconut/palm sugar as sweetener at various fat levels (32%, 34%, and 36%).  Aside from this, Konjac glucomannan and Xanthan gum-based hydrogel with a concentration of 3%, 5%, and 7% was added. Characterization of chocolate quality parameters with the addition of konjac glucomannan-based hydrogel (CKG) and xanthan gum-based hydrogel (CXG) was carried out. Moisture content, melting point, hardness, particle size and brown color analyses were carried out at intervals of 1, 5, 9 days of maturation (crystal growth period). The results showed that the addition of hydrogel influenced the melting point and hardness.  As the period of crystal growth (maturation) increased, the melting point and hardness of the chocolate also increased. Keywords:   Heat Resistant Chocolate, Hydrogel, Konjac Glucomannan, Palm Sugar, Xanthan Gum